2022
DOI: 10.1088/1748-605x/ac9267
|View full text |Cite
|
Sign up to set email alerts
|

Development of cannabidiol nanoemulsion for direct nose to brain delivery: statistical optimization, in vitro and in vivo evaluation

Abstract: Cannabidiol (CBD) is a prescribed drug for epilepsy but has low oral bioavailability and gastric instability. Because of the direct link between the nasal cavity and the central nervous system, intranasal administration of CBD as nanoemulsions which are the small sized lipid carriers seem to improve the bioavailability. CBD-nanoemulsions (NEs) were made using Capryol 90, Tween 80, and Transcutol P as oil, surfactant, and co-surfactant, respectively, following aqueous titration approach. Then, using the Box–Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, Capryol ® 90 and, even more, PGMC possess the ability to spontaneously form clear emulsions when mixed with surfactants with high HLB, such as polysorbates (Tween ® ). Both have been extensively investigated for the development of nanoemulsion and SNEDDS, as well as microemulsions and SMEDDS [ 27 , 28 , 29 , 30 ]. The emulsion formed must be clear and limpid and must not allow the drug to precipitate [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Capryol ® 90 and, even more, PGMC possess the ability to spontaneously form clear emulsions when mixed with surfactants with high HLB, such as polysorbates (Tween ® ). Both have been extensively investigated for the development of nanoemulsion and SNEDDS, as well as microemulsions and SMEDDS [ 27 , 28 , 29 , 30 ]. The emulsion formed must be clear and limpid and must not allow the drug to precipitate [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…When delivered at the same dose with the same formulation (PEG 400-ES), the AUC of CBD was around 2-fold higher with intravenous administration than with intranasal administration [ 65 ]. Ahmed and colleagues [ 66 ] also showed that the plasma AUC of intranasal CBD delivery (3.1 mg) was approximately half that of intravenous CBD delivery. However, the brain AUC was around 2-fold higher after intranasal administration of a CBD nanoemulsion formulation compared with intravenous or intranasal delivery of non-formulated CBD.…”
Section: Novel Routes Of Cbd Administrationmentioning
confidence: 99%
“…In dogs, CBD administered intranasally (20 mg) resulted in a C max ~66% and an AUC ~22% of those of oral administration (100 mg) [ 26 ]. The T max with intranasal CBD ranged between 20 and 30 min among studies [ 26 , 65 , 66 ].…”
Section: Novel Routes Of Cbd Administrationmentioning
confidence: 99%
“…Potentially, those cannabinoid-based formulations not initially developed for ocular administration could be considered for this purpose, providing they are compatible with the requisites of ophthalmic administration. Despite the unfavorable physicochemical properties of cannabinoids, successful cannabinoid encapsulation with adequate physicochemical properties of the resulting nanocarrier was achieved with polymeric NPs [130][131][132]; SLNs [133][134][135]; nanostructured lipid carriers [136]; NEs [137]; micelles [138][139][140]; microemulsions [141]; ethosomes [142]; pickering emulsions [143]; silica NPs [144]; and carbon nanotubes [145], to mention a few.…”
Section: Other Cannabinoid Advanced Vehiculation Strategies and Consi...mentioning
confidence: 99%